Strategies of Human T-Cell Leukemia Virus Type 1 for Persistent Infection: Implications for Leukemogenesis of Adult T-Cell Leukemia-Lymphoma - Yasunaga, Jun-ichirou (Frontiers in Microbiology, 2020)
Human T-cell leukemia virus type 1 (HTLV-1) establishes persistent infection in vivo in two distinct ways: de novo infection and clonal proliferation of infected cells. Two viral genes, Tax and HTLV-1 bZIP factor (HBZ) play critical roles in viral transcription and promotion of T-cell proliferation, respectively. Tax is a potent transactivator not only for viral transcription but also for many cellular oncogenic pathways, such as the NF-kappaB pathway. HBZ is a suppressor of viral transcription and has the potential to change the immunophenotype of infected cells, conferring an effector regulatory T cell (eTreg)-like signature (CD4+CD25+CCR4+TIGIT+Foxp3+) and enhancing the proliferation of this subset. Reports that mice transgenic for either gene develop malignant tumors suggest that both Tax and HBZ are involved in leukemogenesis by HTLV-1. However, the immunogenicity of Tax is very high, and its expression is generally suppressed in vivo. Recently, it was found that Tax can be expressed transiently in a small subpopulation of adult T-cell leukemia-lymphoma (ATL) cells and plays a critical role in maintenance of the overall population. HBZ is expressed in almost all infected cells except for the rare Tax-expressing cells, and activates the pathways associated with cell proliferation. These findings indicate that HTLV-1 fine-tunes the expression of viral genes to control the mode of viral propagation. The interplay between Tax and HBZ is the basis of a sophisticated strategy to evade host immune surveillance and increase transmission -- and can lead to ATL as a byproduct.